Delayed replantation of avulsed teeth - Adil N; Ahmed S; Jindal M; Arshad S (Wolters Kluwer Medknow Publications, 2007)
Dental injuries are very common and their extent has been classified by Ellis. Avulsion of tooth is a grievous injury and ranges from 1-16% among the traumatic injuries, of which maxillary anterior are commonest. Reimplantation of avulsed teeth is a standard procedure. However, it has certain limitations. Most often their management is very challenging. In this case report we are presenting the management of maxillary incisors by replantation after 36 hrs in a 12 year old girl.